Habitual food consumption, eating behavior and meal-timing among Jordanian adults with elevated Blood pressure: a cross-sectional population-based study - Buthaina Alkhatib; Islam Al-Shami; Lana M. Agraib (Blood Pressure)
Background The prevalence of elevated blood pressure (BP) has been raised worldwide. Food consumption, eating habits, and nutritional lifestyle related to meal timing, skipping meals, and meal contents have recently received more attention in studies on BP and metabolic syndrome. Purpose: This study evaluated the association between habitual food consumption, eating behavior, and meal timing with BP among Jordanian adults.Methods A cross-sectional study included 771 Jordanian adults. A food frequency questionnaire was completed. Data about eating habits, meal timing, and emotional eating were collected. BP was measured.Results The prevalence of less than recommended intake of vegetables, milk, protein, and fruits was higher in participants with elevated BP (69.2%, 90.2%, 58.9%, and 25.5%, respectively) as compared to the normal BP group (p < 0.001). Consuming vegetables and milk less than the recommended was reported to significantly increase the likelihood of elevated BP by OR= (1.60, and 2.75 (95%CI: 1.06-2.40; 1.62-4.66). Hence, consuming more than recommended fruit reduced the risk of elevated BP by OR = 0.56 (95%CI: 0.38-0.82). A 63.2% of elevated BP participants have three meals daily, a higher percentage of intake of one (23.5%) and two (45.7%) snacks. However, they had a higher percentage of morning eaters (50.7%), had lunch between 1:00-6:00 PM (92.7%), and had dinner between 6:00 and 9:00 PM (68.1%).Conclusions Although Jordanian adults with elevated BP appear to have healthy eating habits and meal timing and frequency, their habitual food consumption falls short of the daily recommendations for milk, fruits, vegetables, and protein.